The integrated management system in the bakery industry of Leskovac - Veličković Jasmina; Arsić Jovana; Staletović Maja (Trendovi u Poslovanju)
Of all the factors influencing people's health, nutrition takes the most important place. The normal growth and development, the resilience towards infections and diseases, aging before time and development of common activities are just some of the aspects of the influence of regular and safe nutrition on a man. A large number of disesases appearing with people is conditioned exactly by the nutrition with foodstuffs not safe nor regular. Cereal products, even bread as the basic life foodstuff, belong to the gifts nature offers to a man with the application of technology and certain engagement. In order to get high quality and safe, short-lived and semi-permanent products, apart from the use of regulated and standardized equipment, that is, the procedures of quality systems ISO 9001:2015, it is necessary to provide the food safety system (HACCP), which determines, evaluates and controls risks important for the safety of made products. The field of bread and pastry production is very sensitive from the aspect of quality analysis and the application of the newest standards, which requires taking of a number of measures - from providing and receiving raw material to the distribution of finished products. The aim of the paper is the review of the integrated management system in the bakery industry, with the emphasis on the quality of products.